Design and implement medicinal plant application (SITONA) on android platform - Kurniastuti, Ima; Winarningsih, Wiwik; Ghofirin, Mohammad (International Journal of Scientific Research and Management (IJSRM), 2022)
The aim of this research is to design and build an android-based medicinal plant application or SITONA. SITONA consists of a directory of medicinal plants in Indonesia. SITONA has several features that function to empower health and strengthen the economy through an in-app marketplace. The steps in the study were literature study, requirement analysis, design flowchart, design interface, and implement application. First step was literature study, a step to collect information about medicinal plants in Indonesia. Requirement analysis consist of software requirement analysis and hardware requirement analysis. Design flowchart step has aim to design process flown in application. Design interface step has output such as interface in every feature in application. Implement application was a step to implement design flowchart and design interface into android application. Implement application using android studio. The last step is testing application using black box testing. Result of testing application show that application is running well and application ready in use.